A Relative Review of Operation Theater Environment Management : Operation Theater Environment Management - Fayyaz, Maria; Sohaib Tahir, Hafiz Muhammad; Muneer, Bushra; Naeem, Usra; Akram, Fazeelat; Islam, Beenish (Pakistan Journal of Health Sciences, 2023)
The operation theater is a very critical area, and everything needs to be done in an ordinate manner to maintain efficacy. However, managers are needed to maintain the functionality of the OT suite. An OR manager is responsible for many things, like scheduling OT but most importantly, OT efficiency. An OR manager faces different challenges during management of an OR suite. These vary from organization to organization. The most common types of diversity found in OT are cultural diversity, religious diversity, organizational and environmental diversity, and so on. An OR manager should manage these diversities ethically and professionally to overcome an ethical dilemma. OR managers should encourage ethical behavior to improve OT efficacy and effectiveness, but change may reduce or hinder OT effectiveness due to resistance to change. Ideally, the OR manager should manage sustainability to reduce resistance to change without compromising OT efficacy or inducing socio-ethical conflicts among the OR team. For this, OR teams are managed in such a way to facilitate high-quality teamwork and promote good communication skills. However, many barriers hinder communication, which may cause misconceptions and compromise efficacy. Many tactics and strategies are used to reduce these conflicts peri-operatively and OT performance indicators are used to determine the efficiency. To increase productivity, efficiency, and effectiveness as needed while lowering personnel costs, an OR manager organizes and schedules the OT.